Spanish as a resource in the acquisition of English as a second language - Ana María Pérez-Cabello; Michelle Teresa Quinn (Peoples' Friendship University of Russia (RUDN University), 2024)
The use of the mother tongue in foreign language lessons has always generated a wide debate on whether the use of L1 prevents students from learning a L2. This research shows what teachers of English as L2 in Spain think about this topic. First, we review the reasons to exclude the use of Spanish, as well as the reasons for its inclusion. This approach includes linguistic, social, and cultural factors intrinsic to the teaching/learning process. Information is collected using a mixed method approach. On the one hand, a questionnaire is designed to identify patterns and trends regarding the use of Spanish in the English classroom considering factual, behavioural, and attitudinal data. Each section is linked to research objectives. On the other, three specific qualitative methods are used: personal interviews, small focus group discussions and extension written narratives, where 12 questions are composed as a basis for the realisation of these three methods. The results of the study suggest that a prudent and judicious use of Spanish does not prevent or hinder the development of English learning in students. On the contrary, in many cases, it facilitates it since it provides the teacher with a powerful pedagogical resource. The study posits that the judicious employment of Spanish within the classroom setting yields positive outcomes and advocates for increased flexibility in its utilisation. However, it simultaneously points to the imperative that this flexibility should not detract from the primary objective of English language acquisition. This study has theoretical and practical implications in the design of formation syllabi for in-service and future teachers of L2 in L1 contexts.